Validation and optimization of criteria for manual smear review following automated blood cell analysis in a large university hospital - Busadee Pratumvinit (2018)
Context. - Each laboratory should have criteria for manual smear review that limit workload without affecting patient care. The International Consensus Group for Hematology Review established guidelines for action after automated blood cell analysis in 2005. Objective. - To compare the consensus group criteria with our laboratory criteria and optimize them for better efficiency. Design. - A total of 2114 first-time samples were collected consecutively from daily workload and were used to compare 2 criteria as well as establish the optimized criteria. Another set of 891 samples was used to validate the optimized criteria. All samples were run on either Sysmex XE-5000 or Coulter LH750 hematology analyzers and were investigated by manual smear review. The efficiency of each set of criteria was compared and optimized to obtain better efficiency, an acceptable review rate, and a low false-negative rate. Results. - From 2114 samples, 368 (17.40%) had positive smear results. Compared with that of our laboratory criteria, the efficiency of the consensus group criteria was higher (83.63% versus 78.86%, P < .001), the review rate was higher (29.33% versus 22.37%, P < .001), and the false-negative rate was lower (2.22% versus 8.09%, P < .001). After optimizing the rules, we obtained an efficiency of 87.13%, a review rate of 24.22%, and a false-negative rate of 2.98%. We validated the optimized criteria with another set of samples, and the efficiency, review rate, and false-negative rate were 87.32%, 25.25%, and 1.12%, respectively. Conclusions. - Each laboratory should verify the criteria for smear review, based on the International Consensus Group for Hematology Review, and optimize them to maximize efficiency.